The wooden «Chasuble Madonnas» from Ger, IX, Targasona and Talló. About the iconography of Catalan Madonna statues in the Romanesque period - Tim Heilbronner (Locvs Amoenvs, 2008)
Numerous wooden Madonna statues of the Romanesque style have survived from medieval Catalonia, which show the Virgin as sedes sapientiae. The thematized exemplars from Ger (second half 12th century), IX (last third 12th century), Targasona (early 13th century) attract the attention of today's viewer by an iconographic peculiarity. Explicitly, they show the enthroned Mother of God, as it will be pointed out, in the priestly chasuble. The chasuble most probably represents Mary's significance as symbol of the hierarchical or institutionalized church and also alludes to the conception of Mary being interpreted as priest or ministerial priest, which became more and more popular in the 12th century. The throne representations of the statues from Ger and IX, which refer undoubtedly to the famous episcopal throne from the Girona Cathedral by its formal structure, will be related to this significant meaning, too. The iconographic type of the Catalan «Chasuble Madonna» is not to be found in the art of wood carving first, but in Romanesque mural paintings in the Pyrenean Valleys of North-West Cataloia. The historical and cultural sphere, which could have been responsible for the development and dissemination of this Madonna type respectively, will be discussed in the present article in the context of the 11th and 12th century church reform in Catalonia.